Three essays on corporate finance - Pang, Caiji (2014)
This thesis consists of 3 essays on corporate finance. In the first essay, We examine the effect of CEO severance pay on the likelihood of CEO turnover. We find that severance pay reduces both the frequency and performance sensitivity of turnover. Moreover, we find that these reductions are especially pronounced when, conditional on poor past performance, there remain considerable uncertainties about CEOs' competence. Our findings suggest that severance pay protects CEOs against the risk of dismissal when performance is poor but may only be temporarily so. In addition, we show that variations in the quality of corporate governance do not significantly alter the relation between severance pay and turnover rate, suggesting that the protection effect of severance pay is orthogonal to the effects of corporate governance on CEO turnover. In the second essay, we separate the reverse merger targets into public shell companies and public non-shell companies and confirm that the non-shell targets have distinct difference from shell targets in firms’ characteristics. We further find that non-shell based RM companies outperform shell based RM companies in terms of short-run stock return, long-run stock return and long-run operating performance. We then provide evidence to show that timely PIPE financing after the reverse merger transaction is critical to RM companies’ future performance. The outperformance of non-shell based RM companies can be explained by their better ability to secure PIPE investments within 6 months after the transaction. Last but not least, by matching the RM companies with a group of penny stock IPO companies, we find that reverse merger companies are not inherently worse than those IPO companies. In the third essay, by using a cross-country sample, I find that the presence of former politicians serving as independent directors (PIDs) in a company is associated with certain firm-level, industry-level and country-level characteristics. Furthermore, I investigate the effects of PIDs on the firm’s future performance and find that PIDs have an adverse effect on firm’s operating performance as well as firm value. This phenomenon is especially severe if a firm is in a heavy regulated industry. However, the adverse effect of PIDs can be mitigated if a firm is in a country with a legal system providing more protection to shareholders, or in a country with better corporate governance provisions.